Pengaruh Green Intellectual Capital Dan Financial Non Distress Terhadap Sustainable Growth - Agnia Cantika Kartikasari; Christina Dwi Astuti (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the effect of green intellectual capital nad financial non-distress on sustainable growth. This study uses secondary data, the data used in the form of sustainability report of companies listed on the Indonesia Stock Exchange. The type of research used in this study is causal research, namely research that aims to find a causal relationship of the variables studied to answer research questions. The samples used in this study are consumer cyclicals companies that are listed on the Indonesia Stock Exchange in the period of 2019-2021. Data were collected using purposive sampling. The total number of companies in the study sample is 140 companies with a study period of 3 years, resulting in 109 samples after outliers. The results of the study using linear regression analysis, descriptive statistic, and classic assumption test indicate that Green structural capital and Green relational has a significant positive effect on sustainable growth. Then the results of linear regression analysis indicate that financial non-distress does affect sustainable growth.